Upaya Promotif dan Preventif Fisioterapi Terhadap Kejadian Shoulder Impingement Syndrome (SIS) pada Pemain Bola Voli - Yuliadarwati, Nungki Marlian; Devika, Triana; Pinurti, Hayu (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Counseling on dynamic warm-up and prevention of Shoulder Impingement Syndrome (SIS) in volleyball players is carried out with the aim of promoting physiotherapy to increase knowledge and awareness about the importance of warm-up before exercising so as to increase knowledge and minimize the incidence of shoulder injuries or SIS. Methods this counseling activity is in the form of lectures, questions and answers and simple practices carried out at the volleyball court of the Sultan Imanuddin Pangkalan Bun Hospital, 16 participants with evaluation instruments using a closed questionnaire. The results of the evaluation showed a 75% increase in participant knowledge about SIS and dynamic warm-up practices, as well as a 50% percentage of awareness of the importance of warm-up. This activity emphasizes the importance of continuing education to prevent injury and improve the performance of volleyball players.